Stuck in the Past? The Influence of a Leader’s Past Cultural Experience on Group Culture and Positive and Negative Group Deviance - Kim, Yeun Joon; Toh, Soo Min (Academy of Management Journal, 2019)
Extant research on the antecedents of cultures has posited that cultures result from the internal and external changes experienced by the group (the functionality perspective) and from a group leader’s personal values and personality traits (the leader–trait perspective). The current study proposes another important but neglected antecedent of cultures: a leader’s past cultural experience. Specifically, we theorize that group leaders enact cultures based on their past cultural experiences, essentially transferring cultures from their former groups to their current groups. Two studies, one in the field (Study 1) and another in the laboratory (Study 2), reveal that the levels of cultural tightness in current groups are predicted by group leaders’ past experience with cultural tightness in their former groups in which they were followers. This relationship becomes stronger when the group leaders identified with or had longer tenure in their former groups. In addition, the cultural tightness that leaders transferred from their former groups to their current groups influences negative (counterproductive work behavior) and positive (promotive and prohibitive voice) forms of group deviance. The theoretical and managerial implications of our findings for leadership and culture are discussed.